ANALISIS PERSEPSI DAN DAMPAK PENERAPAN QANUN LEMBAGA KEUANGAN SYARIAH PADA PERBANKAN DI ACEH - Anzira, Raudhatul; Farma, Junia; Umuri, Khairil (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2022)
This study aims to examine the public's perception of banking institutions and the impact of the implementation of Qanun no. 11 of 2018 on the growth of sharia banking customers. This research is a field research, and the nature of this research is descriptive qualitative. The data collection technique is through interviews with bank employees and the people of Bireuen Regency, Aceh. Based on the results of the study, it shows that public perception, viewed from the aspect of understanding and satisfaction is relatively low, this is due to the lack of socialization related to the bank's operational system and the lack of banking responses in responding to public complaints related to bank services. When viewed from the aspect of trust, the majority of the community supports the LKS Qanun so that the regional economy runs Islamically. Therefore, Islamic banking is expected to be able to carry out socialization and education, as well as expand networks and improve human resources.